Noncovalent Immobilization of Pectinesterase (Prunus armeniaca L.) onto Bentonite - Karakus, Emine; Ozler, Aynur; Pekyardimci, Sule (INFORMA HEALTHCARE, 2008)
In this work, pectinesterase isolated from Malatya apricot was immobilized onto acid-treated bentonite surface by simple adsorption at pH 9.0. The properties of free and immobilized enzyme were defined. The effect of various factors such as pH, temperature, heat, and storage stability on immobilized enzyme were investigated. Optimum pH and temperature were determined to be 9.0 and 50 degrees C, respectively. Kinetic parameters of the immobilized enzyme ( Km and Vmax values) were also determined as 0.51 mM of the Km and 14.6 mu mol min(-1) mg(-1) of the Vmax. No drastic change was observed in the Km value after immobilization. The Vmax value of immobilized enzyme was 8.4-fold bigger than those of free enzyme. Thermal and storage stability experiments were carried out. The patterns of heat stability indicated that the immobilization process tends to stabilize the enzyme. The properties of the immobilized enzyme were compared to those of the free enzyme.
Keywords: bentonite; pectinesterase; purification; non-covalent immobilization; adsorption; iocemical characterization; PECTIN METHYLESTERASE; TOMATO PECTINESTERASE; CANDIDA-RUGOSA; BRAMLEY APPLE; LIPASE; ENZYME; FRUIT; INACTIVATION; EXTRACTION; Biotechnology & Applied Microbiology; Engineering; Materials Science